Suitability of paediatric legislation beyond the USA and Europe: a qualitative study on access to paediatric medicines - Albrecht Jahn; Rosa Jahn; Anna Volodina (BMJ Public Health)
Background Paediatric legislation has contributed to better access to appropriate treatments in the European Union and the USA by requiring paediatric research in return for financial incentives. This study explored whether similar policies could improve access to medicines in other countries.Methods We conducted 46 interviews with representatives from healthcare practice, patient organisations and health authorities from six countries (Australia, Brazil, Canada, Kenya, Russia and South Africa) as well as multinational pharmaceutical companies exploring their views regarding access barriers to paediatric medicines. Emphasis was placed on regulation-related barriers and the effect of the COVID-19 pandemic. Where participants were familiar with paediatric legislation, views regarding its relevance for domestic context were explored in depth.Results Insufficient paediatric research and development, regulatory hurdles and reimbursement constraints were reported to be relevant access barriers in all studied settings. In the absence of marketing registration or reimbursement, access to paediatric medicines was associated with increased legal, financial and informational barriers. Brazil, Kenya, Russia and South Africa additionally described overarching deficiencies in medicines provision systems, particularly in procurement and supply. The COVID-19 pandemic was said to have reduced regulatory hurdles while further heightening global access inequalities.Views regarding paediatric legislation were mixed. Concerns regarding the implementation of such policies focused on regulatory resource constraints, enforceability and potential reduction of industry activity.Conclusions The study findings suggest that paediatric legislation may be most impactful in mature health systems and should be accompanied by measures addressing access barriers beyond marketing registration. This could include strengthening domestic manufacturing capacities and technology transfer for medicines with high public health relevance. Ideally, legislative changes would build on global harmonisation of paediatric legislation, which could be achieved through existing WHO structures.